Pre-Export Activity: The First step in Internationalization - Wiedersheim-Paul, Finn; Olson, Hans C; Welch, Lawrence S (Journal of International Business Studies, 1978)
In this article we develop a model that stresses the importance of a firm's activities and “pre-export” behavior for the export start. Of special importance in the model are factors such as information, characteristics of the decision-maker, the enterprise environment, and the extraregional expansion of the firm. The model is based both on more “traditional” research in international business and recent developments in location theory.